Development of Interactive Media to Improve CNC Machine Malfunction Handling Skills of TU 3A Based on Immersive Gamification - Raihan Ramadhan; Rizky Ema Wulansari; Eko Indrawan; Dony Novaliendry; Dimas Aulia Saputra (Jurnal Penelitian Pendidikan IPA, 2025)
This research was conducted to design and produce an electronic module (e-module) for CNC Programming that integrates a project-based learning (PjBL) approach with an immersive gamification strategy, optimized for use on Android-based devices. The study employed a Research and Development (R&D) methodology, adopting the 4D framework consisting of the stages of define, design, develop, and disseminate. Data were obtained from expert validators, lecturers, and students to evaluate the e-module in terms of its validity, practicality, and effectiveness. The validation results indicated that the e-module achieved excellent validity, with average scores of 0.917 for media quality and 0.950 for material quality. The practicality evaluation yielded ratings of 96.94% from lecturers and 91.90% from students, both categorized as very practical. The effectiveness test produced an N-Gain value of 0.69, which reflects a moderate improvement in students’ learning performance. Furthermore, the t-test analysis (Sig. 0.001 < 0.05; t-count 3.806 > t-table value) demonstrated a statistically significant difference between the experimental and control groups. Overall, the developed PjBL-based e-module with immersive gamification features was found to be valid, practical, and effective, serving as an interactive learning medium that fosters student engagement and aligns with 21st-century educational demands.